"Affirming" journey: Narrative review and practice considerations on gender affirming care. Issue 7 (30th March 2022) - Mills, Alex R.; Astle, Kevin; Frazier, Cheyenne C.
Abstract: There is a growing interest in the healthcare community to focus on the healthcare needs of lesbian, gay, bisexual, transgender, or genderqueer (LGBTQ) patients, particularly transgender and gender diverse (TGD) patients. TGD individuals have historically experienced rejection and mistreatment by healthcare providers yet have significant health needs, highlighting the need for providing affirming care. Medication therapy for TGD individuals involves many nuances and special considerations for managing concomitant therapies and drug interactions. Additionally, approaches to caring for TGD patients involve both medical interventions as well as social and legal processes. Pharmacists can assist and facilitate the care for TGD patients through a variety of mechanisms. This narrative review describes strategies to recognize and address many aspects of the care for TGD individuals, including destigmatizing care, affirmation strategies, and an overview of therapeutic misconceptions and concerns. Ultimately, this manuscript serves as a guide for pharmacists to care holistically for TGD patients.